Importance of donor ethnicity/race matching in unrelated adult and cord blood allogeneic hematopoietic cell transplant. Issue 2 (February 2014) - Ustun, Celalettin; Bachanova, Veronika; Shanley, Ryan; MacMillan, Margaret L.; Majhail, Navneet S.; Arora, Mukta; Brunstein, Claudio; Wagner, John E.; Weisdorf, Daniel J.
Abstract Donor race matching (both recipient and donor belonging to the same race) might be a factor in outcomes of donor allogeneic hematopoietic cell transplant (alloHCT). A total of 858 patients who underwent umbilical cord blood (UCB) (475 patients: 202 double UCB and 273 single UCB) or unrelated donor (URD) (383 patients) alloHCT between January 1995 and December 2010 were studied. Most patients were Caucasian (87%), followed by Asians (4%), African Americans (3%), Hispanics (3%), mixed race (3%) and American Indians (< 1%). Caucasians constituted 88% of the donor grafts; Caucasians were the most common race of the donor grafts among all races except for Asians. As a result, Caucasians were much more likely to have a race-matched donor than ethnic minorities (91% vs. 33%, p < 0.01). Donor race matching did not affect non-relapse mortality, relapse, acute or chronic graft-versus-host disease or overall survival. Acknowledging the limitations of this study (mainly, self-reported race information and small number of ethnic minorities), at present there are no data supporting that donor race should be considered a factor in donor selection.